2021
DOI: 10.2217/cer-2020-0165
|View full text |Cite
|
Sign up to set email alerts
|

Reasons and factors associated with inconclusiveness of systematic reviews about interventions for neuropathic pain

Abstract: Aim: Systematic reviews (SRs) are frequently inconclusive. The aim of this study was to analyze factors associated with conclusiveness of SRs about efficacy and safety of interventions for neuropathic pain (NeuP). Materials & methods: The study protocol was registered in the PROSPERO database (No. CRD42015025831). Five electronic databases (Medical Literature Analysis and Retrieval System Online, Cochrane Database of Systematic Reviews, Cumulative Index for Nursing and Allied Health Literature, Database of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The same applies to systematic reviews which are frequently inconclusive 36 . Conclusiveness of evidence was higher in systematic reviews which included more participants and randomized controlled trials (RCTs), searched more databases, conducted meta-analysis, and examined the quality of evidence 37 . diabetes reported an eye examination within the previous 2 years, whereas only 50% reported that their feet were examined by a health care professional in the previous year 39 .…”
Section: Implementation Of Guidelines Into Clinical Practicementioning
confidence: 99%
“…The same applies to systematic reviews which are frequently inconclusive 36 . Conclusiveness of evidence was higher in systematic reviews which included more participants and randomized controlled trials (RCTs), searched more databases, conducted meta-analysis, and examined the quality of evidence 37 . diabetes reported an eye examination within the previous 2 years, whereas only 50% reported that their feet were examined by a health care professional in the previous year 39 .…”
Section: Implementation Of Guidelines Into Clinical Practicementioning
confidence: 99%
“…Finally, a new tool to assess discordance should take into consideration the conclusiveness, or the stability of the results, of the SRs under question [62][63][64][65]. For example, the Cochrane logo shows the summary results from a conclusive SR called "Antenatal corticosteroids for accelerating fetal lung maturation for women at risk of preterm birth" [66].…”
Section: Future Researchmentioning
confidence: 99%